2016
DOI: 10.1007/s40617-016-0159-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Pyramidal Training Model on the Implementation of Trial-Based Functional Analysis: a Partial Replication

Abstract: We employed a pyramidal training model (PTM) to teach staff to correctly implement and collect data for trialbased functional analysis (TBFA) in simulated situations. First, we trained four behavioral consultants (BCs) in a group format, who each trained one behavior technician (BT) in an individual format. We utilized a non-concurrent multiple baseline design to evaluate the effect of the training. During generalization probes, participants implemented TBFA with a novel problem behavior. This study will contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…The second main finding of the study showed that, based on the pyramid model, secondary participants could also perform MSWO sessions with high treatment reliability and generalize the skill they acquired separately. These results are similar to previous studies' findings based on the pyramid model (Alnemary et al, 2017;Ducharme et al, 2009;.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The second main finding of the study showed that, based on the pyramid model, secondary participants could also perform MSWO sessions with high treatment reliability and generalize the skill they acquired separately. These results are similar to previous studies' findings based on the pyramid model (Alnemary et al, 2017;Ducharme et al, 2009;.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to these basic findings, there are points to be emphasized regarding this research process. For example, in some of the studies based on the pyramid model, data were collected through role-playing in the baseline sessions (Alnemary et al, 2017). In others, these sessions were planned with real persons (individuals with special needs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hands‐on approach to skill training is unique in that pre‐service teachers learn a new EBP while simultaneously learning how to teach others that same EBP through modeling, role‐play, and explicit instruction from an expert trainer. Pyramidal training methods have been used a variety of settings such as at home (e.g., Alnemary, Wallace, Alnemary, Gharapetian, & Yassine, ; Haberlin, Beauchamp, Agnew, & O'Brien, ), in schools (e.g., Kunnavatana et al, ; Suhrheinrich (), and university settings (e.g., Martocchio & Rosales, ).…”
Section: Introductionmentioning
confidence: 99%